Barium sulfate surface treatment aid, preparation method, application and barium sulfate filled polyolefin elastomer material

As a barium sulfate surface treatment additive, the mPEG-MMA block copolymer prepared by oxyanionic polymerization solves the problem of insufficient dispersion and performance of barium sulfate in the polymer in the prior art, and achieves efficient dispersion and performance improvement of barium sulfate in polyolefin elastomer materials.

CN119613263AActive Publication Date: 2025-03-14BEIJING HONGXIANGJU SCIENCE & TRADE CO LTD +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411583148.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-03-14
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

The binding effect of the existing barium sulfate surface treatment additives and barium sulfate is limited, the operation is complex and costly, which affects the dispersion and performance of barium sulfate in polymers.

Method used

The mPEG-MMA block copolymer composed of polyethylene glycol monomethyl ether (mPEG) and methyl methacrylate (MMA) was prepared by oxyanionic polymerization, and serves as a barium sulfate surface treatment additive to improve the compatibility and dispersion of barium sulfate with the polymer.

Benefits of technology

The full dispersion and bonding of barium sulfate in the polyolefin elastomer material is achieved, which significantly improves the mechanical properties and elasticity of the material, and reduces the operating complexity and cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613263A_ABST
    Figure CN119613263A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of polymer composite materials, and discloses a barium sulfate surface treatment auxiliary agent, a preparation method and application of the barium sulfate surface treatment auxiliary agent and a barium sulfate filled polyolefin elastomer material. The molar ratio of methoxypolyethylene glycol to methyl methacrylate is 1: (1-4), and the theoretical molecular weight of the barium sulfate surface treatment aid is 300-600. The mPEG-MMA block copolymer composed of methoxypolyethylene glycol (mPEG) and methyl methacrylate (MMA) is prepared through oxygen anion polymerization and can serve as a barium sulfate surface treatment auxiliary to be fully combined on the surface of barium sulfate, the hydrophilicity of the barium sulfate is reduced, the characteristic that barium sulfate is difficult to be compatible with a polymer is overcome, and the service life of the barium sulfate is prolonged. The barium sulfate subjected to surface treatment can be fully combined with polyolefin elastomer components, highly uniform dispersion is realized, and the overall performance of the barium sulfate filled polyolefin elastomer material can be further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer composite materials, and in particular relates to a barium sulfate surface treatment auxiliary agent, a preparation method, an application, and a barium sulfate-filled polyolefin elastomer material. Background Art

[0002] Barium sulfate is an inorganic salt compound. It plays an important role in the preparation of polymer materials due to its unique high stability, chemical inertness, low odor, low emission, and excellent radiation shielding properties. Compounding polymers with barium sulfate can not only reduce costs, but also improve the mechanical properties, weather resistance and flame retardancy of the material, while giving the material radiation shielding function. More importantly, barium sulfate's good chemical stability and biological safety enable it to be used as a filling component of medical polymer elastomer materials. Many medical polymer materials with radiation imaging functions use barium sulfate as the main filling component.

[0003] However, as an inorganic compound, barium sulfate has a strong surface polarity and significant hydrophilicity, which leads to poor compatibility between barium sulfate and polymers. Untreated barium sulfate particles are difficult to disperse in polymers and mostly exist in polymers in aggregated structures. The inorganic characteristics of barium sulfate lead to unsatisfactory overall performance of the material after it is filled and compounded with polymers, and barium sulfate is easily enriched and precipitated on the surface of the material, which also has an adverse effect on the appearance of the material. Especially for elastomeric materials, barium sulfate that is not fully dispersed will also have a significant adverse effect on the elasticity and fatigue resistance of the material. In order to overcome these problems, it is particularly important to surface treat barium sulfate.

[0004] After surface treatment, groups or functional groups compatible with polymers can be introduced on the surface of barium sulfate particles, thereby enhancing the interaction between the barium sulfate particles and the polymer and improving the dispersion stability. In addition, surface treatment can also change the surface properties of barium sulfate particles, such as reducing surface energy, improving wettability, etc., inhibiting the self-aggregation tendency of barium sulfate particles filled in polymers, and further improving the dispersion effect of barium sulfate particles in polymers. At present, barium sulfate products used to fill polyolefin elastomers are usually surface treated.

[0005] For example, Chinese patent application with publication number CN112662059A discloses a barium sulfate masterbatch for plastic pipes and a preparation method thereof, wherein sulfur is first dispersed on the surface of the barium sulfate, SBS is further hot-melt dispersed on the surface of the barium sulfate with the aid of paraffin, and the SBS is vulcanized at a suitable temperature. The surface of the crushed barium sulfate fine powder is firmly coated with the vulcanized SBS, and then mixed with a polypropylene carrier resin and granulated to obtain a masterbatch.

[0006] However, the existing barium sulfate surface treatment additives and treatment methods on the market still have some shortcomings. On the one hand, the combination effect of some surface treatment additives and barium sulfate is limited, resulting in poor treatment effect; on the other hand, some treatment methods are complicated to operate and costly, which limits their application in industrial production. In addition, some treatment methods may also have adverse effects on the physical properties of barium sulfate, such as reducing its density or stability.

[0007] Therefore, in view of the shortcomings of existing barium sulfate surface treatment, the development of new and efficient barium sulfate surface treatment additives and corresponding methods of use has important practical significance and application prospects. By designing the molecular structure of the modified additive, it can be fully and efficiently combined with barium sulfate, thereby changing the hydrophilic and high polarity characteristics of the barium sulfate surface and strengthening the binding effect between barium sulfate and polymers, which is the key to the design and application development of barium sulfate surface additives.

[0008] In view of this, the present invention is proposed. Summary of the invention

[0009] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a barium sulfate surface treatment auxiliary agent, a preparation method, an application, and a barium sulfate-filled polyolefin elastomer material. The present invention prepares an mPEG-MMA block copolymer composed of polyethylene glycol monomethyl ether (mPEG) and methyl methacrylate (MMA) through oxyanion polymerization, which can be used as a barium sulfate surface treatment auxiliary agent to be fully combined on the surface of barium sulfate, overcome the property that barium sulfate is difficult to be compatible with polymers, so that the surface-treated barium sulfate can be fully combined with the polyolefin elastomer component and achieve highly uniform dispersion, further improving the overall performance of the barium sulfate-filled polyolefin elastomer material.

[0010] In order to solve the above technical problems, the basic concept of the technical solution adopted by the present invention is:

[0011] The present invention provides a barium sulfate surface treatment auxiliary agent mPEG-MMA composed of polyethylene glycol monomethyl ether (mPEG) and methyl methacrylate (MMA) prepared by oxyanion polymerization, and according to the characteristics of the auxiliary agent, the method of using it in the surface modification of barium sulfate is clarified, and the method of using the corresponding modified barium sulfate in polyolefin elastomer is clarified. Through verification, it can be confirmed that mPEG-MMA is successfully synthesized and prepared according to the expected structure, and can be fully combined with barium sulfate and improve the surface characteristics of barium sulfate through the designed method. Further comparison confirms that the polyolefin composite material to which barium sulfate surface-treated with mPEG-MMA is added has better mechanical properties and more ideal elasticity. The process of surface treating barium sulfate with mPEG-MMA is simple and easy, and the obtained surface-treated barium sulfate can also be prepared by conventional twin-screw melt extrusion and compounding with polyolefin elastomer to obtain the corresponding elastomer composite material, which is easy to realize continuous industrial production conversion as a whole.

[0012] In a first aspect, the present invention provides a barium sulfate surface treatment aid, comprising a block copolymer composed of polyethylene glycol monomethyl ether mPEG and methyl methacrylate MMA, wherein the molar ratio of the polyethylene glycol monomethyl ether to the methyl methacrylate is 1:1-4, and the theoretical molecular weight of the barium sulfate surface treatment aid is 300-600.

[0013] In a further embodiment, in the block copolymer, the average number of repeating units of polyethylene glycol monomethyl ether is 4-5, and the average number of repeating units of methyl methacrylate is 1-4.

[0014] The mPEG-MMA of the present invention is a block copolymer of ethylene glycol and acrylate, wherein the ester group can react with the hydroxyl group on the surface of barium sulfate at high temperature, so that the mPEG-MMA is fully attached to the surface of barium sulfate, thereby modifying the barium sulfate. At the same time, the polyether structure in the polyethylene glycol segment can also be combined with the hydroxyl group on the surface of barium sulfate in the form of hydrogen bonds, thereby achieving the coating of the surface treatment auxiliary agent mPEG-MMA on the surface of barium sulfate, minimizing the exposed hydrophilic groups on the surface of barium sulfate, improving the affinity of barium sulfate with polymer parts, and reducing its self-aggregation tendency.

[0015] The present invention obtains a barium sulfate surface treatment auxiliary agent with an expected molecular weight by controlling the addition ratio of polyethylene glycol monomethyl ether mPEG and methyl methacrylate MMA. The mPEG-MMA block copolymer of the present invention has a specific repeating unit structure and a narrow relative molecular mass distribution. After barium sulfate is surface treated with mPEG-MMA, barium sulfate can be fully combined with mPEG-MMA, and the hydrophilicity of barium sulfate is significantly reduced, and the overall performance of the corresponding filled polyolefin elastomer material is further significantly improved, thereby improving the use effect of the barium sulfate filled polyolefin elastomer material in different application scenarios.

[0016] In a second aspect, the present invention provides a method for preparing a barium sulfate surface treatment additive, comprising:

[0017] (1) heating and evacuating a container, then filling it with an inert gas, and cooling the container to room temperature;

[0018] (2) maintaining an inert gas environment, adding polyethylene glycol monomethyl ether into a container, then adding a solvent, and shaking to dissolve it;

[0019] (3) adding sodium hydride or potassium hydride into the container to react;

[0020] Preferably, sodium hydride is added into the container;

[0021] Preferably, the reaction is carried out at 20-30° C. for 1-3 hours;

[0022] (4) mixing methyl methacrylate and a solvent to form a solution, and adding the solution dropwise into a container to react;

[0023] Preferably, the temperature is maintained at 20-30° C. and the reaction is continued for at least 2 hours, more preferably 2-4 hours; the minimum reaction time is 2 hours, and more time has no significant effect on the results.

[0024] (5) adding methanol dropwise into the container to terminate the reaction and collecting the reaction product;

[0025] (6) removing the solvent from the reaction product to obtain the barium sulfate surface treatment additive mPEG-MMA.

[0026] In a further embodiment, in step (1), the container is heated to 100-200°C.

[0027] In a further embodiment, the inert gas may be a common inert gas, such as nitrogen.

[0028] As a more specific scheme, in step (1), the prepared container is fully sealed and connected to a vacuum device via a conduit. The container is heated to 100-200°C while being evacuated to a vacuum. The vacuum is then turned off, the conduit is connected to a nitrogen supply system, nitrogen is filled into the container, and the container is cooled to room temperature. The above operation is repeated three times.

[0029] This step is intended to fully remove oxygen, carbon dioxide, and moisture in the reaction space to prevent the above substances from destroying the ion initiator and causing the active center to be deactivated.

[0030] In a further embodiment, in step (2), the weight of the added solvent is 2-4 times the weight of polyethylene glycol monomethyl ether;

[0031] Preferably, the solvent is selected from tetrahydrofuran.

[0032] In the oxyanion polymerization described in the present invention, a solvent environment with a certain polarity is required. At the same time, the corresponding synthetic raw materials and products also have requirements on the solubility parameters of the solvent. Therefore, tetrahydrofuran is selected as the solvent in the present invention.

[0033] Preferably, the average molecular weight of the polyethylene glycol monomethyl ether is 200.

[0034] Among conventional products of polyethylene glycol monomethyl ether, the molecular weight of 200 is the lowest. Limited by the molecular weight of the final product being between 300-600, products with a higher molecular weight of polyethylene glycol monomethyl ether cannot be selected.

[0035] As a more specific scheme, in step (2), without destroying the nitrogen environment in the container, mPEG with an average molecular weight of 200 is added to the prepared container, and then tetrahydrofuran (THF) is added as a solvent at a weight of 2-4 times the weight of mPEG, and the mPEG is fully dissolved by shaking.

[0036] As a solvent, THF has low viscosity and high solubility, and can provide good fluidity. At the same time, THF has moderate polarity, which avoids the problems of initiator aggregation and low initiation efficiency. It is a necessary solvent for polar monomers to carry out oxyanion polymerization.

[0037] In a further embodiment, in step (3), the molar ratio of sodium hydride or potassium hydride to polyethylene glycol monomethyl ether is 1:1.

[0038] Preferably, sodium hydride is used.

[0039] In the present invention, sodium hydride is an initiator used in oxyanion polymerization and a component that promotes the start of the reaction. The polymerization reaction first forms an active center after sodium hydride reacts with polyethylene glycol monomethyl ether. Methyl methacrylate is added in the presence of the active center, so that each active center reacts with methyl methacrylate at the same time, and the molecular chains in each active center are polymerized synchronously to form a final product. In this process, it is necessary to control the molecular weight of the final product by controlling the molecular weight of the initiator and the polyethylene glycol monomethyl ether to reach 1:1, and by controlling the molecular weight ratio of methyl methacrylate to the initiator.

[0040] The molecular weight of the final product is 300-600, which is designed based on the fact that the surface treatment additive will eventually be used in the treatment of barium sulfate. Surface treatment additives with too high molecular weight have poor fluidity and are solid under normal conditions. It is difficult to achieve sufficient surface treatment of barium sulfate through simple stirring and heating processes. In surface treatment additives with too low molecular weight, since the mPEG component is fixed at a molecular weight of 200, the content of the MMA component is relatively small, and the surface treatment effect and function of the additive are relatively unsatisfactory.

[0041] In a further embodiment, in step (4), the molar ratio of polyethylene glycol monomethyl ether to methyl methacrylate is 1:1-4;

[0042] Preferably, in step (4), the weight of the solvent in the solution is 2-4 times the weight of methyl methacrylate;

[0043] More preferably, the solvent is selected from tetrahydrofuran.

[0044] As a more specific solution, in step (4), sodium hydride in the same molar amount as mPEG is added to the container, that is, the weight of the added sodium hydride is 12% of the weight of mPEG, and the reaction is carried out at 20-30° C. for 1-3 hours.

[0045] Alternatively, add potassium hydride in the same molar amount as mPEG into the container, that is, the weight of potassium hydride added is 20% of the weight of mPEG, and react at 20-30° C. for 1-3 hours.

[0046] The preferred solution is sodium hydride.

[0047] Prepare MMA with 1-4 times the molar amount of mPEG in the container, that is, the weight of MMA is 0.5-2 times that of mPEG, and mix it with THF with 2-4 times the weight of MMA to form a solution. Add the solution dropwise into the container. Maintain the temperature at 20-30°C, continue the reaction for 2 hours, then drop methanol into the container to terminate the reaction and collect the reaction product.

[0048] This reaction is a typical oxyanion polymerization, using the oxyanion generated by sodium hydride in a polar solvent as an active center to initiate the polymerization of acrylate monomers. Combined with the use of this method, it is possible to synthesize mPEG-MMA block copolymers with specific structures and narrow relative molecular weight distribution at room temperature.

[0049] In a further scheme, in step (6), the collected product is subjected to vacuum distillation to remove THF, ethanol is added for washing, and then vacuum distillation is performed again, and finally the obtained product is centrifuged to remove the solvent, thereby obtaining the barium sulfate surface treatment additive mPEG-MMA.

[0050] According to the feed ratio and the average molecular weight of mPEG, in the mPEG-MMA segment synthesized by the present invention, the average number of repeating units of mPEG is 4.5, the number of repeating units of MMA is 1-4, and the theoretical molecular weight of the overall product is between 300-600.

[0051] In a third aspect, the present invention provides a use of the above-mentioned barium sulfate surface treatment auxiliary agent or the above-mentioned preparation method in the preparation of surface-treated barium sulfate powder.

[0052] In a fourth aspect, the present invention provides a method for preparing a surface-treated barium sulfate powder, comprising:

[0053] Take barium sulfate powder, mix it with the barium sulfate surface treatment auxiliary agent described in the first aspect or the barium sulfate surface treatment auxiliary agent prepared by the preparation method described in the second aspect, and stir and mix at high speed;

[0054] Then put it into a high temperature environment of 90-110°C for reaction for 3-5 hours; then stir it at a high speed to obtain surface treated barium sulfate powder.

[0055] Preferably, the weight of the barium sulfate surface treatment additive is 0.5-15wt% of the weight of the barium sulfate powder;

[0056] Preferably, the speed of the high-speed stirring is 1000-2000rpm;

[0057] Preferably, the average particle size of the barium sulfate powder is 100-400 nm.

[0058] As a specific solution, the method for preparing the surface-treated barium sulfate powder includes:

[0059] (1) Mixing of barium sulfate and surface additives:

[0060] Take barium sulfate powder without any surface chemical treatment and with an average particle size of 100-400 nm, mix it with 0.5-15wt% of its own weight of mPEG-MMA, put it into a high-speed mixer, and mix it thoroughly for 3-6 minutes at a speed of 1000-2000rpm.

[0061] The molecular weight of the mPEG-MMA designed by the present invention is between 300 and 600, the molecular weight is moderate, the overall viscosity is not high, and the mPEG-MMA and barium sulfate can be fully mixed within a short mixing time, providing a basis for subsequent modification reactions.

[0062] (2) Reaction combination:

[0063] The barium sulfate powder mixed with mPEG-MMA is placed in a high temperature environment of 90-110°C to allow the surface additive to react with the barium sulfate for 3-5 hours.

[0064] mPEG-MMA is a block copolymer of ethylene glycol and acrylate, in which the ester group can react with the hydroxyl group on the surface of barium sulfate at high temperature, so that mPEG-MMA can fully adhere to the surface of barium sulfate and achieve the modification of barium sulfate. At the same time, the polyether structure in the polyethylene glycol segment can also combine with the hydroxyl group on the surface of barium sulfate in the form of hydrogen bonds, thereby achieving the coating of the surface treatment additive mPEG-MMA on the surface of barium sulfate, minimizing the exposed hydrophilic groups on the surface of barium sulfate, improving the affinity of barium sulfate with polymer parts, and reducing its tendency to self-aggregate. Since the polyether structure and polyester structure in mPEG-MMA account for a large proportion, the surface treatment additive and barium sulfate can fully react only under sufficient heating conditions, and the reaction method is simple and easy.

[0065] (3) Mixing and dispersion

[0066] The barium sulfate that has completed the surface reaction and bonding is put into the high-speed mixer again, and stirred at a speed of 1000-2000 rpm for 3-6 minutes to finally obtain the surface-treated barium sulfate powder.

[0067] In a fifth aspect, the present invention provides a barium sulfate filled polyolefin elastomer material, comprising:

[0068] SBS 0-90wt%, SEBS 0-95wt%, POE 0-95wt%, PP 0-45wt%, PE 0-45wt%, 5-50wt% of surface-treated barium sulfate powder prepared by the preparation method described in the fourth aspect, and 0.2-1wt% of antioxidant, wherein the sum of SBS, SEBS and POE is 50-98wt%;

[0069] Preferably, the antioxidant is selected from at least one of antioxidant 1010, antioxidant 1076, antioxidant 168, and antioxidant 626.

[0070] The polyolefin elastomer material of the present invention comprises at least one polymer selected from butadiene-styrene copolymer (SBS), hydrogenated styrene-butadiene block copolymer (SEBS), ethylene-α-olefin copolymer elastomer (POE), at least one polymer selected from polypropylene (PP) and polyethylene (PE), the surface-treated barium sulfate powder provided by the present invention, and an antioxidant.

[0071] Compared with similar materials prepared with ordinary barium sulfate, the filled polyolefin elastomer material prepared with mPEG-MMA surface-treated barium sulfate of the present invention has more excellent mechanical properties, higher resilience and more ideal batch resistance.

[0072] In a sixth aspect, the present invention provides a method for preparing a barium sulfate-filled polyolefin elastomer material, comprising:

[0073] (1) mixing at least one of SBS, SEBS and POE with at least one of PP and PE, surface-treated barium sulfate powder and an antioxidant;

[0074] In this process, all raw materials can be added into a low-speed mixer and mixed at a speed of 150 rpm for 2 minutes to obtain a blended mixture.

[0075] (2) Then, the product is melt-extruded through a twin-screw extruder and pelletized to obtain a barium sulfate-filled polyolefin elastomer material.

[0076] The process can use the existing conventional twin-screw extruder and extrusion conditions. For example, the selected twin-screw extruder has an aspect ratio of 48 to 56:1, the vacuum extraction pressure value of the metering section is set to -0.85 to -0.95 MPa, the temperature of each section of the screw is set in the range of 130 to 230°C, the main engine speed is set to 200 to 400 rpm, the blended mixture is added to the twin-screw extruder from the main feed port for melt extrusion, and the corresponding barium sulfate-filled polyolefin elastomer material is obtained after pelletizing.

[0077] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art:

[0078] (1) The present invention prepares mPEG-MMA block copolymers with a relative molecular weight of 300-600 by controlling the addition amounts of mPEG and MMA through oxyanion polymerization, and applies them to the surface treatment of barium sulfate, giving full play to the characteristics of low molecular weight and rich polyether structure and polyester structure, so that it can be quickly and evenly mixed with barium sulfate, and the surface treatment of barium sulfate can be achieved under heating conditions, and the reaction method is simple and easy.

[0079] (2) The present invention utilizes the organic properties of mPEG-MMA itself to combine with the hydroxyl groups on the surface of barium sulfate and coat the surface of barium sulfate, thereby minimizing the hydrophilic groups exposed on the surface of barium sulfate and fully combining with the surface of barium sulfate, significantly overcoming the poor compatibility of barium sulfate with polymers, so that the barium sulfate after surface treatment can be fully combined with the polyolefin elastomer component and achieve highly uniform dispersion.

[0080] (3) The use of surface-treated barium sulfate improves the overall performance of the barium sulfate-filled polyolefin elastomer material. Compared with similar materials prepared with ordinary barium sulfate, the filled polyolefin elastomer material prepared with mPEG-MMA surface-treated barium sulfate of the present invention has better mechanical properties, higher resilience and more ideal batch resistance.

[0081] (4) All types of equipment involved in the present invention are commercially available, various types of raw materials are widely available, and the overall solution is easy to implement.

[0082] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0083] The accompanying drawings are part of the present invention and are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention, but do not constitute an improper limitation of the present invention. Obviously, the drawings described below are only some embodiments. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the accompanying drawings:

[0084] Figure 1 This is a scanning electron microscope (SEM) photograph of the barium sulfate filled polyolefin elastomer material prepared according to the preparation method described in Example 4.

[0085] It should be noted that these drawings and textual descriptions are not intended to limit the conceptual scope of the present invention in any way, but are intended to illustrate the concept of the present invention for those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION

[0086] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. The following embodiments are used to illustrate the present invention but are not used to limit the scope of the present invention.

[0087] The detection method adopted by the present invention is as follows:

[0088] 1. Average molecular weight determination:

[0089] The relative molecular weight of the sample was tested using a liquid chromatography-mass spectrometer. Chromatographic grade methanol was used as the mobile phase in the test, and the injection volume was controlled at 5 μL. The sample was ionized using the TIC anode source ion ionization mode, and the molecular weight of the sample was obtained by combining the multi-reaction level test method.

[0090] 2. Thermal gravimetric test:

[0091] Thermodynamic gravimetric analyzer (TGA) was used for thermal gravimetric determination. The sample was placed in a TGA special crucible. The test was carried out under nitrogen conditions. The test temperature range was 30°C to 800°C, and the heating rate was 10°C / min.

[0092] 3. Water contact angle test:

[0093] Take a small amount of the powder to be tested, place it in a mold, and press it into a tablet under a pressure of 10MPa. Use a contact angle tester to operate a micro syringe to drop water drops onto the surface of the silica tablet. Keep the first picture after complete dripping. The angle between the tangent line of the water drop surface and the sample in the picture is the contact angle.

[0094] 4. Tensile strength:

[0095] The tensile properties are tested according to GB / T 528-2009. The sample is cut into a standard dumbbell-shaped sample with a thickness of 2±0.2mm and a working area width of 6mm. The sample is fixed on the fixture of the electronic tensile machine, and the extensometer is clamped on the sample working area. The extensometer is 25mm away and stretched at a rate of 500mm / min until the sample breaks. The tensile properties of the sample, such as tensile strength, 300% tensile stress and elongation at break, are recorded.

[0096] 5. Tear strength:

[0097] The tear strength is tested according to GB / T 529-2008. The sample is cut into a standard rectangular sample with a thickness of 2±0.2mm using a standard cutter. The sample is fixed on the fixture of the electronic tensile machine and the tear test is carried out at a rate of 500mm / min until the sample breaks. The tear strength of the sample is recorded.

[0098] 6. Deformation recovery rate under 300% strain:

[0099] The sample is cut with a cutter according to the requirements of GB / T 528-2009 standard to cut out a standard dumbbell-shaped sample with a thickness of 2±0.2mm and a working area width of 6mm. After marking an area of ​​25mm in length in the working area of ​​the spline, it is fixed on the fixture of the electronic tensile machine, and the extensometer is aligned with the marked line and clamped on the sample. Stretching is performed at a rate of 500mm / min. After the strain reaches 300% (that is, the total length in the marked area reaches 100mm), the stretching is stopped and the spline is removed. After 24 hours, the length of the marked area is measured as L, and the deformation recovery rate is calculated according to R=(L-25) / (100-25)×100%.

[0100] Example 1 Preparation of barium sulfate surface treatment additive

[0101] Place four 2000ml flasks in four oil baths, set the oil bath temperature to 120°C, fully seal the flasks, and connect the flasks to the vacuum pump with a catheter. During the heating process, turn on the vacuum pump and gradually evacuate all four flasks to a vacuum. Turn off the vacuum 2 minutes after the flask temperature reaches above 100°C. Then connect the flasks to the nitrogen bottle in turn with a catheter, fill each flask with nitrogen, and wait for all flasks to cool to room temperature. Repeat the above process 3 times to complete the preparation of 4 reaction vessels.

[0102] Use a syringe to add 50g of mPEG with an average molecular weight of 200 to the prepared flask, then use a syringe to add 100g of THF as a solvent, and repeatedly shake for 2 minutes to fully dissolve the mPEG. Perform the same operation on all four flasks. Inject 6g of sodium hydride into each of the four flasks and react for 3 hours in an oil bath at 20°C.

[0103] Prepare 25g, 50g, 75g and 100g of MMA respectively, put them into 4 beakers No. 1-4, then add 100g, 200g, 300g and 400g of THF into the 4 beakers No. 1-4 respectively, so that the MMA in the 4 beakers is fully mixed with THF to form a solution. Add the MMA solution in beakers No. 1-4 to the 4 flasks respectively, and keep all flasks in an oil bath at 20°C for 2 hours. After the reaction is over, methanol is dripped into the 4 flasks to terminate the reaction. After opening the flasks, collect the reaction products, add the products to the rotary evaporator in turn, remove THF by vacuum distillation, add ethanol for washing and vacuum distillation again. The obtained 4 products are centrifuged to remove the solvent, and the barium sulfate surface additive mPEG-MMA with theoretical molecular weights of 300, 400, 500 and 600 are obtained.

[0104] The four products were subjected to mass spectrometry detection using a liquid chromatography-mass spectrometer to analyze their average molecular weight and molecular structure, and the results are shown in Table 1. From the results, it can be seen that the main molecular composition of the obtained products is consistent with the design, and the measured average molecular weight is basically consistent with the theoretical molecular weight.

[0105] Table 1

[0106]

[0107] Example 2

[0108] Place a 2000ml flask in an oil bath, set the temperature of the oil bath to 200°C, fully seal the flask, and connect the flask to a vacuum pump with a catheter. During the heating process, turn on the vacuum pump and gradually evacuate the flask to a vacuum. 2 minutes after the flask temperature reaches above 190°C, turn off the vacuum. Then connect the flask to a nitrogen bottle with a catheter, fill the flask with nitrogen, and wait for the container to cool to room temperature. Repeat the above process 3 times to complete the preparation of the reaction vessel.

[0109] Use a syringe to add 100g of mPEG with an average molecular weight of 200 into the prepared flask, then use a syringe to add 400g of THF as a solvent, and repeatedly shake for 2 minutes to fully dissolve the mPEG. Then inject 20g of potassium hydride into the flask and react for 3 hours under 30°C oil bath conditions.

[0110] Prepare 100g of MMA, put it in a beaker, and then add 200g of THF to the beaker to fully mix the MMA and THF in the beaker to form a solution. Add the MMA solution in the beaker dropwise into the flask, and keep the flask in an oil bath at 30°C for 4 hours. After the reaction is over, methanol is dropped into the flask to terminate the reaction. After opening the flask, collect the reaction product, add the product to a rotary evaporator, remove THF by vacuum distillation, add ethanol for washing, and vacuum distill again. Centrifuge the obtained product to remove the solvent to obtain a barium sulfate surface additive mPEG-MMA with a theoretical molecular weight of 400.

[0111] Take 1000g of barium sulfate powder without any surface chemical treatment and with an average particle size of 400nm, divide it into 5 parts, numbered 1-5, add 2g, 6g, 12g, 20g, 30g of mPEG-MMA with a theoretical molecular weight of 400 to powders 1-5, respectively, stir and mix them briefly, and then put the 5 mixtures into a high-speed stirrer, and mix them for 6 minutes at a speed of 1000rpm. Put the 5 kinds of barium sulfate powders after high-speed stirring and mixing into an oven at 110℃, take them out after being placed for reaction for 3 hours, and then put them into a high-speed stirrer, stir them for 3 minutes at a speed of 2000rpm, and finally obtain 5 kinds of surface-treated barium sulfate powders, wherein the amount of the surface treatment auxiliary agent mPEG-MMA is 1wt%, 3wt%, 6wt%, 10wt%, 15wt% of the weight of the barium sulfate powder.

[0112] The five surface-treated barium sulfate powders and the untreated barium sulfate powder were respectively coated with filter paper, and then extracted for 24 hours (about 15-20 minutes of reflux once) using a Soxhlet extractor with cyclohexane as the solvent. The products after extraction were placed in an oven, dried to constant weight at 70°C, and then subjected to thermal weight loss tests. According to the characteristics of barium sulfate powder, the weight loss range can be divided into two ranges: room temperature -120°C and 120-800°C. The weight loss in the former range is caused by the removal of adsorbed water, and the weight loss in the latter range is mainly caused by the removal of chemically bound water and the decomposition of the surface additives bound to barium sulfate. The corresponding results are shown in Table 2.

[0113] Table 2

[0114]

[0115]

[0116] From the data in Table 2, it can be seen that as the amount of mPEG-MMA relative to barium sulfate increases, the weight loss of the corresponding barium sulfate sample in the range of 120-800°C increases, while the weight loss in the range of room temperature -120°C decreases. This result shows that mPEG-MMA is fully and firmly combined with barium sulfate, and on the other hand, it also shows that the hydrophilicity of barium sulfate combined with mPEG-MMA is significantly reduced.

[0117] Example 3

[0118] Place a 1000ml flask in an oil bath, set the temperature of the oil bath to 160°C, fully seal the flask, and connect the flask to a vacuum pump with a catheter. During the heating process, turn on the vacuum pump and gradually evacuate the flask to a vacuum. 2 minutes after the flask temperature reaches above 150°C, turn off the vacuum. Then connect the flask to a nitrogen bottle with a catheter, fill the flask with nitrogen, and wait for the container to cool to room temperature. Repeat the above process 3 times to complete the preparation of the reaction vessel.

[0119] Use a syringe to add 40g of mPEG with an average molecular weight of 200 into the prepared flask, then use a syringe to add 120g of THF as a solvent, and shake repeatedly for 2 minutes to fully dissolve the mPEG. Then inject 4.8g of sodium hydride into the flask and react for 2 hours in an oil bath at 25°C.

[0120] Prepare 60g of MMA, put it in a beaker, and then add 180g of THF to the beaker to fully mix the MMA and THF in the beaker to form a solution. Add the MMA solution in the beaker dropwise into the flask, and keep the flask in an oil bath at 25°C for 3 hours. After the reaction is over, methanol is dropped into the flask to terminate the reaction. After opening the flask, collect the reaction product, add the product to a rotary evaporator, remove THF by vacuum distillation, add ethanol for washing, and then vacuum distill again. Centrifuge the obtained product to remove the solvent to obtain a barium sulfate surface additive mPEG-MMA with a theoretical molecular weight of 500.

[0121] Take 200g of barium sulfate powder without any surface chemical treatment and with an average particle size of 200nm, add 10g of the above mPEG-MMA with a theoretical molecular weight of 500 into the powder, and after simple stirring and mixing, put the mixture into a high-speed stirrer and mix it thoroughly for 3 minutes at a speed of 2000rpm. Put the barium sulfate powder after high-speed stirring and mixing into a 90°C oven, place it for reaction for 5 hours, take it out, put it into a high-speed stirrer again, and stir it thoroughly for 6 minutes at a speed of 1000rpm to finally obtain surface-treated barium sulfate powder, wherein the amount of the surface treatment auxiliary agent mPEG-MMA is 5wt% of the weight of the barium sulfate powder.

[0122] Part of the surface treated barium sulfate powder was taken for particle size detection, and part of the treated barium sulfate powder was pressed into thin sheets at 15 MPa for water contact angle test. Untreated barium sulfate powder was treated in the same way for control test, and the results are shown in Table 3.

[0123] Table 3

[0124]

[0125]

[0126] From the results in Table 3, it can be seen that the average particle size of barium sulfate after surface treatment has basically not changed, but the water contact angle has been significantly improved, which shows that the hydrophilicity of barium sulfate can be significantly reduced after surface treatment of barium sulfate with mPEG-MMA.

[0127] Example 4

[0128] Place a 2000ml flask in an oil bath, set the temperature of the oil bath to 130°C, fully seal the flask, and connect the flask to a vacuum pump with a catheter. During the heating process, turn on the vacuum pump and gradually evacuate the flask to a vacuum. Turn off the vacuum 2 minutes after the flask temperature reaches above 120°C. Then connect the flask to a nitrogen bottle with a catheter, fill the flask with nitrogen, and wait for the container to cool to room temperature. Repeat the above process 3 times to complete the preparation of the reaction vessel.

[0129] Use a syringe to add 200g of mPEG with an average molecular weight of 200 into the prepared flask, then use a syringe to add 500g of THF as a solvent, and repeatedly shake for 2 minutes to fully dissolve the mPEG. Then inject 24g of sodium hydride into the flask and react for 1.5 hours in an oil bath at 30°C.

[0130] Prepare 100g of MMA, put it in a beaker, and then add 300g of THF to the beaker to fully mix the MMA and THF in the beaker to form a solution. Add the MMA solution in the beaker dropwise into the flask, and keep the flask in an oil bath at 30°C for 3.5 hours. After the reaction is over, methanol is dropped into the flask to terminate the reaction. After opening the flask, collect the reaction product, add the product to a rotary evaporator, remove THF by vacuum distillation, add ethanol for washing, and vacuum distill again. Centrifuge the obtained product to remove the solvent to obtain a barium sulfate surface additive mPEG-MMA with a theoretical molecular weight of 300.

[0131] Take 2000g of barium sulfate powder without any surface chemical treatment and with an average particle size of 100nm, add 160g of the above mPEG-MMA with a theoretical molecular weight of 300 into the powder, and after simple stirring and mixing, put the mixture into a high-speed stirrer and mix it thoroughly for 5 minutes at a speed of 1500rpm. Put the barium sulfate powder after high-speed stirring and mixing into an oven at 100°C, place it for reaction for 4 hours, take it out, put it into a high-speed stirrer again, and stir it thoroughly for 5 minutes at a speed of 1600rpm to finally obtain surface-treated barium sulfate powder, wherein the amount of the surface treatment auxiliary agent mPEG-MMA is 8wt% of the weight of the barium sulfate powder.

[0132] According to the formula shown in Table 4, a total of 2000 g of materials were weighed for each formula, and the raw materials of 6 components were added into a low-speed mixer in sequence, and mixed at a speed of 150 rpm for 2 minutes to obtain 6 blended mixtures.

[0133] Table 4-1

[0134]

[0135]

[0136] Table 4-2

[0137]

[0138] A twin-screw extruder with an aspect ratio of 48:1 was selected, the screw was divided into 12 zones, the vacuum extraction pressure value of the metering section was set to -0.90 MPa, the temperature of each section of the screw was set to 130°C, 190°C, 200°C, 200°C, 210°C, 210°C, 200°C, 200°C, 205°C, 210°C, 210°C, 220°C, the main engine speed was set to 200rpm, the mixed raw materials were added to the twin-screw extruder from the main feed port for melt blending, and the corresponding barium sulfate filled polyolefin elastomer material was obtained after pelletizing. The mechanical properties and deformation recovery of the obtained material were tested, and the results are shown in Table 5.

[0139] Table 5-1

[0140]

[0141] Table 5-2

[0142]

[0143]

[0144] Result analysis: It can be seen from Table 5 that compared with the untreated barium sulfate, the polyolefin elastomer material using surface-treated barium sulfate has better mechanical properties and more ideal resilience. With the increase of the barium sulfate filling amount, the performance advantage of the sample with barium sulfate after surface treatment with mPEG-MMA is more obvious.

[0145] Example 5

[0146] Place a 5000ml flask in an oil bath, set the temperature of the oil bath to 180°C, fully seal the flask, and connect the flask to a vacuum pump with a catheter. During the heating process, turn on the vacuum pump and gradually evacuate the flask to a vacuum. 2 minutes after the flask temperature reaches above 160°C, turn off the vacuum. Then connect the flask to a nitrogen bottle with a catheter, fill the flask with nitrogen, and wait for the container to cool to room temperature. Repeat the above process 3 times to complete the preparation of the reaction vessel.

[0147] Use a syringe to add 250g of mPEG with an average molecular weight of 200 into the prepared flask, then use a syringe to add 750g of THF as a solvent, and shake repeatedly for 2 minutes to fully dissolve the mPEG. Then inject 30g of sodium hydride into the flask and react for 2.5 hours in an oil bath at 25°C.

[0148] Prepare 375g of MMA, put it in a beaker, and then add 750g of THF to the beaker to fully mix the MMA and THF in the beaker to form a solution. Add the MMA solution in the beaker dropwise into the flask, and keep the flask in an oil bath at 25°C for 2.5 hours. After the reaction is over, methanol is dropped into the flask to terminate the reaction. After opening the flask, collect the reaction product, add the product to a rotary evaporator, remove THF by vacuum distillation, add ethanol for washing, and then vacuum distill again. Centrifuge the obtained product to remove the solvent to obtain a barium sulfate surface additive mPEG-MMA with a theoretical molecular weight of 500.

[0149] Take 10000g of barium sulfate powder without any surface chemical treatment and with an average particle size of 300nm, add 500g of the above mPEG-MMA with a theoretical molecular weight of 500 into the powder, and after simple stirring and mixing, put the mixture into a high-speed stirrer and mix it thoroughly for 4 minutes at a speed of 1800rpm. Put the barium sulfate powder after high-speed stirring and mixing into an oven at 105°C, place it for reaction for 4 hours, take it out, put it into a high-speed stirrer again, and stir it thoroughly for 6 minutes at a speed of 1200rpm to finally obtain surface-treated barium sulfate powder, wherein the amount of the surface treatment auxiliary agent mPEG-MMA is 5wt% of the weight of the barium sulfate powder.

[0150] According to the formula shown in Table 6, a total of 2000 g of materials were used for each formula, and the raw materials of the four components were weighed. The four raw materials of the four components were added into a low-speed mixer in sequence, and mixed at a speed of 150 rpm for 2 minutes to obtain four blended mixtures.

[0151] Table 6

[0152]

[0153] A twin-screw extruder with an aspect ratio of 52:1 was selected, the screw was divided into 13 zones, the vacuum extraction pressure value of the metering section was set to -0.90 MPa, the temperature of each section of the screw was set to 130°C, 190°C, 200°C, 200°C, 210°C, 210°C, 200°C, 200°C, 205°C, 205°C, 210°C, 210°C, 220°C, the main engine speed was set to 400rpm, the mixed raw materials were added to the twin-screw extruder from the main feed port for melt blending, and the corresponding barium sulfate filled polyolefin elastomer material was obtained after pelletizing. The mechanical properties and deformation recovery of the obtained material were tested, and the results are shown in Table 7.

[0154] Table 7

[0155]

[0156] Example 6

[0157] Place a 1000ml flask in an oil bath, set the temperature of the oil bath to 170°C, fully seal the flask, and connect the flask to a vacuum pump with a catheter. During the heating process, turn on the vacuum pump and gradually evacuate the flask to a vacuum. 2 minutes after the flask temperature reaches above 150°C, turn off the vacuum. Then connect the flask to a nitrogen bottle with a catheter, fill the flask with nitrogen, and wait for the container to cool to room temperature. Repeat the above process 3 times to complete the preparation of the reaction vessel.

[0158] 80 g of mPEG with an average molecular weight of 200 was added to the prepared flask using a syringe, and then 200 g of THF was added as a solvent using a syringe, and the mixture was shaken repeatedly for 2 minutes to fully dissolve the mPEG. 9.6 g of sodium hydride was injected into the flask, and the mixture was reacted in an oil bath at 20°C for 2.5 hours.

[0159] Prepare 80g of MMA, put it in a beaker, and then add 160g of THF to the beaker to fully mix the MMA and THF in the beaker to form a solution. Add the MMA solution in the beaker dropwise into the flask, and keep the flask in an oil bath at 20°C for 2 hours. After the reaction is over, methanol is dropped into the flask to terminate the reaction. After opening the flask, collect the reaction product, add the product to a rotary evaporator, remove THF by vacuum distillation, add ethanol for washing, and vacuum distill again. Centrifuge the obtained product to remove the solvent to obtain a barium sulfate surface additive mPEG-MMA with a theoretical molecular weight of 400.

[0160] Take 1000g of barium sulfate powder without any surface chemical treatment and with an average particle size of 200nm, add 120g of the above mPEG-MMA with a theoretical molecular weight of 400 to the powder, and after simple stirring and mixing, put the mixture into a high-speed stirrer and mix it thoroughly for 5 minutes at a speed of 1400rpm. Put the barium sulfate powder after high-speed stirring and mixing into an oven at 95°C, place it for reaction for 5 hours, take it out, put it into a high-speed stirrer again, and stir it thoroughly for 4 minutes at a speed of 1600rpm to finally obtain surface-treated barium sulfate powder, wherein the amount of the surface treatment auxiliary agent mPEG-MMA is 12wt% of the weight of the barium sulfate powder.

[0161] According to the formulation shown in Table 8, 2000 g of raw materials were weighed, and the raw materials were added into a low-speed mixer in sequence, and mixed at a speed of 150 rpm for 2 minutes to obtain a blended mixture.

[0162] Table 8

[0163]

[0164] A twin-screw extruder with an aspect ratio of 56:1 was selected. The screw was divided into 14 zones. The vacuum extraction pressure value of the metering section was set to -0.90 MPa. The temperatures of each section of the screw were set to 130°C, 190°C, 200°C, 200°C, 210°C, 210°C, 200°C, 200°C, 205°C, 205°C, 210°C, 210°C, 210°C, 220°C. The main engine speed was set to 300 rpm. The mixed raw materials were added to the twin-screw extruder from the main feed port for melt blending. After pelletizing, the corresponding barium sulfate-filled polyolefin elastomer material was obtained. After hot pressing the material, the material was observed by scanning electron microscopy. As shown in the attached figure, Figure 1 As shown, a large number of particles of hundreds of nanometers can be observed uniformly distributed on the surface of the material, which directly illustrates the role of mPEG-MMA in improving the dispersibility of barium sulfate in polyolefin elastomer.

[0165] Comparative Example 1

[0166] The difference of this comparative example and implementation 2 is that the MMA weight of preparation is 400g, and it is 800g to mix the used THF of MMA in a beaker.The solution formed joins in the mPEG solution in the same way, reacts.Finally obtaining the barium sulfate surface additive mPEG-MMA with a theoretical molecular weight of 1000.When barium sulfate powder is processed, using the mPEG-MMA with this molecular weight of 1000, obtaining surface-treated barium sulfate is numbered 6-10.The barium sulfate powder of gained surface treatment is also subjected to thermogravimetric test after extraction, and the result is as shown in table 9.

[0167] Table 9

[0168]

[0169] From the data in Table 9, it can be seen that under the same dosage, the barium sulfate treated with mPEG-MMA with a molecular weight of 400 loses more weight in the range of 120-800°C, which means that after the molecular weight of mPEG-MMA increases to 1000, its efficiency in binding with barium sulfate is lower. This is because, on the one hand, as the molecular weight of mPEG-MMA increases, the number of mPEG-MMA molecules decreases under the same weight. More importantly, the surface treatment additive with too high molecular weight has poor fluidity and is solid under normal conditions. It is difficult to achieve sufficient surface treatment of barium sulfate through simple stirring and heating processes, which leads to a decrease in the efficiency of mPEG-MMA binding to barium sulfate.

[0170] Comparative Example 2

[0171] The difference between this comparative example and Example 4 is that when treating the barium sulfate powder, mPEG-MMA is replaced with an equal mass of surfactant potassium salt of dodecyl alcohol ether phosphate to prepare the surface-treated barium sulfate.

[0172] Then, according to the formulation in Table 4-2, the surface-treated barium sulfate in the surface-treated barium sulfate-filled polyolefin elastomer formulation 1-3 was replaced with the barium sulfate surface-treated with the above-mentioned potassium salt of dodecyl alcohol ether phosphate, and the resulting formulations were successively named formulations 9-11.

[0173] The other operations are exactly the same as those in Example 4. The mechanical properties and deformation recovery of the obtained material were tested, and the results are shown in Table 10.

[0174] Table 10

[0175]

[0176] Result analysis: It can be seen from Table 10 that compared with the untreated barium sulfate, the polyolefin elastomer material treated with the surfactant potassium dodecyl alcohol ether phosphate has better mechanical properties and more ideal resilience, but its effect is not as good as that of mPEG-MMA.

[0177] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with the present invention can make some changes or modify the technical contents suggested above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the solution of the present invention.

Claims

1. A barium sulfate surface treatment additive, characterized in that: The invention comprises a block copolymer composed of polyethylene glycol monomethyl ether and methyl methacrylate, wherein the molar ratio of the polyethylene glycol monomethyl ether to the methyl methacrylate is 1:1-4, and the theoretical molecular weight of the barium sulfate surface treatment auxiliary agent is 300-600.

2. The barium sulfate surface treatment auxiliary agent according to claim 1, characterized in that: In the block copolymer, the average number of repeating units of polyethylene glycol monomethyl ether is 4-5, and the number of repeating units of methyl methacrylate is 1-4.

3. A method for preparing a barium sulfate surface treatment additive, characterized in that: include: (1) heating and evacuating a container, then filling it with an inert gas, and cooling the container to room temperature; (2) maintaining an inert gas environment, adding polyethylene glycol monomethyl ether into a container, then adding a solvent, and shaking to dissolve it; (3) adding sodium hydride or potassium hydride into the container to react; Preferably, the reaction is carried out at 20-30° C. for 1-3 hours; (4) mixing methyl methacrylate and a solvent to form a solution, and adding the solution dropwise into a container to react; Preferably, the temperature is maintained at 20-30°C and the reaction is continued for at least 2 hours, more preferably 2-4 hours; (5) adding methanol dropwise into the container to terminate the reaction and collecting the reaction product; (6) removing the solvent from the reaction product to obtain the barium sulfate surface treatment additive mPEG-MMA.

4. The preparation method according to claim 3, characterized in that: In step (1), the container is heated to 100-200°C.

5. The preparation method according to claim 3, characterized in that: In step (2), the weight of the added solvent is 2-4 times the weight of polyethylene glycol monomethyl ether; Preferably, the solvent is selected from tetrahydrofuran; Preferably, the average molecular weight of the polyethylene glycol monomethyl ether is 200.

6. The preparation method according to claim 3, characterized in that: In step (3), the molar ratio of sodium hydride or potassium hydride to polyethylene glycol monomethyl ether is 1:1, preferably, sodium hydride is used; In step (4), the molar ratio of polyethylene glycol monomethyl ether to methyl methacrylate is 1:1-4; Preferably, in step (4), the weight of the solvent in the solution is 2-4 times the weight of methyl methacrylate; Preferably, the solvent is selected from tetrahydrofuran.

7. Use of the barium sulfate surface treatment auxiliary agent as claimed in claim 1 or 2 or the preparation method as claimed in any one of claims 3 to 6 in preparing surface-treated barium sulfate powder.

8. A method for preparing surface-treated barium sulfate powder, characterized in that: include: Take barium sulfate powder, mix it with the barium sulfate surface treatment additive according to claim 1 or 2 or the barium sulfate surface treatment additive prepared by the preparation method according to any one of claims 3 to 6, and stir and mix at high speed; Then put it in a high temperature environment of 90-110°C for reaction for 3-5 hours; then stir it at high speed to obtain surface treated barium sulfate powder; Preferably, the weight of the barium sulfate surface treatment additive is 0.5-15wt% of the weight of the barium sulfate powder; Preferably, the speed of the high-speed stirring is 1000-2000rpm; Preferably, the average particle size of the barium sulfate powder is 100-400 nm.

9. A barium sulfate filled polyolefin elastomer material, characterized in that: include: SBS 0-90wt%, SEBS 0-95wt%, POE 0-95wt%, PP 0-45wt%, PE 0-45wt%, 5-50wt% of surface-treated barium sulfate powder prepared by the preparation method according to claim 8, and 0.2-1wt% of antioxidant, wherein the sum of the amounts of SBS, SEBS and POE is 50-98wt%; Preferably, the antioxidant is selected from at least one of antioxidant 1010, antioxidant 1076, antioxidant 168, and antioxidant 626.

10. A method for preparing a barium sulfate filled polyolefin elastomer material as claimed in claim 9, characterized in that: include: Mixing at least one of SBS, SEBS and POE with at least one of PP and PE, surface-treated barium sulfate powder and an antioxidant; Then, the barium sulfate-filled polyolefin elastomer material is obtained by melt extrusion through a twin-screw extruder and pelletization; Preferably, the temperature of each section of the twin-screw extruder is set to the range of 130-230°C, and the main engine speed is set to 200-400rpm.

Citation Information

Patent Citations

  • Barium sulfate master batch for plastic pipe and preparation method

    CN112662059A

  • Amphipathic block copolymer containing polyisobutylene and polyanion and preparation thereof

    CN102391443A

  • Amphipathic block copolymer containing polyisobutylene and polycation and preparation thereof

    CN102391444A

  • Low-gloss polypropylene composite material and preparation method thereof

    CN103073785A

  • High-performance filling master batch used for plastics, and preparation method thereof

    CN103709495A